(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Brevibacterium spp.that was already isolated from wastewater treatment plant of Petra City, Jordan. While 1 and 2 mM of 3,4-dichloro benzoic acid (3,4-DCBA) were used, the biodegradation rate was 14.5 and 21.25 µM/h, respectively, and the remaining was 58% for both. The remaining ratio to the quantity of 3,4-DCBA used was taken in consideration, as a result, 1 mM concentration of 3,4-DCBA substrate was applied for the rest of experiments because of the remaining amount is 0.58 mM 3,4-DCBA while 1.15 mM remained from 2mM concentration used. Thereafter, Brevibacterium spp was grown in batch cultures using M9 minimal media plus 1 mM concentrations of 3,4-DCBA as carbon and energy source. 3,4-DCBA degradation was optimally achieved at a 37 oC incubation temperature, a pH of 7.0 and an agitation rate of 150 rpm. During carbon starvation, the increased biodegradation potential of Brevibacterium spp. was accompanied by a lessening in the acclimatization period besides enhancement of the biodegradation completion of 3,4-DCBA. The adaptation to 3,4-DCBA not only increased the degradation rate but also managed to reduce the time required for complete 3,4-DCBA degradation from 80 to nearly 40 hours. In conclusion, the acclimatized period, and carbon starvation and other optimal conditions were key factors for the enhancement of the degradation ability of 3,4-DCBA by Brevibacterium spp.